2019
DOI: 10.1016/j.tet.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Chemo- and stereoselective six-membered oxonium ylide formation–[2,3]-sigmatropic rearrangement of 2-diazo-3-ketoesters with dirhodium(II) catalyst and its application to the synthesis of (+)-tanikolide

Abstract: 2-ジアゾ-3-ケトエステルの化学・立体選択的ロジウム(II)触媒オキソニウム イリド形成-[2,3]-シグマトロピー転位反応を基軸とする天然物 (+)-tanikolide および類縁体の全合成 (Total synthesis of (+)-tanikolide and its analogues based on novel chemoand stereoselective rhodium(II)-catalyzed oxonium ylide formation-[2,3]sigmatropic rearrangement of 2-diazo-3-ketoesters)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The 4-benzoyloxy derivative 7k was oxidized within 24 h to afford 8k in 73% yield (entry 10). Oxidation of the benzyloxy-substituted derivative 7l produced 8l in 93% yield; however, this reaction required ditert-butyl-4-methylphenol (BHT) 24,25) to prevent the undesired C-H oxidation at the benzylic position (entry 11). Pyrrolidine-2-methanol 7m, which contained an ethoxycarbonylmethoxy group at the 4-position was oxidized to give 8m in 83% yield after 10 h (entry 12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4-benzoyloxy derivative 7k was oxidized within 24 h to afford 8k in 73% yield (entry 10). Oxidation of the benzyloxy-substituted derivative 7l produced 8l in 93% yield; however, this reaction required ditert-butyl-4-methylphenol (BHT) 24,25) to prevent the undesired C-H oxidation at the benzylic position (entry 11). Pyrrolidine-2-methanol 7m, which contained an ethoxycarbonylmethoxy group at the 4-position was oxidized to give 8m in 83% yield after 10 h (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…We also applied this reaction to the total synthesis of tanikolide. 25) We envisioned that this reaction could be applied to azacycles as an efficient oxidative transformation for the synthesis of lactams. Herein, we report the oxidative cleavage of pyrrolidine-2-methanols 7 to γ-lactams 8 using 2-iodobenzamide 6 as the catalyst (Chart 2b).…”
Section: Introductionmentioning
confidence: 99%
“…Tanikolide, a toxic and antifungal lactone from the cyanobacterium Lnygbya majuscula, [96] intrigues the organic synthesis community due to its antifungal activity and synthetically formidable quaternary carbon. [97][98][99][100][101][102][103][104][105][106][107][108][109] Yakura's group reported a total synthesis of (+)-Tanikolide utilizing dirhodium(II)-catalyzed [2,3]-sigmatropic rearrangement of an oxonium ylide derived from a diazo compound 127 (Figure 16a). The route involved key steps such as olefin metathesis, tosylhydrazone formation, cyclic alkene generation, and NHC-catalyzed ring-expansion lactonization, culminating in the total synthesis of (+)-Tanikolide (Figure 16).…”
Section: Tanikolidementioning
confidence: 99%
“…Tanikolide, a toxic and antifungal lactone from the cyanobacterium Lnygbya majuscula , [96] intrigues the organic synthesis community due to its antifungal activity and synthetically formidable quaternary carbon [97–109] . Yakura's group reported a total synthesis of (+)‐Tanikolide utilizing dirhodium(II)‐catalyzed [2,3]‐sigmatropic rearrangement of an oxonium ylide derived from a diazo compound 127 (Figure 16a).…”
Section: Figurementioning
confidence: 99%
“…Metal-carbene species can be generated from the corresponding α-diazoketones or α-diazoesters, but systematic studies of the differences in their reactivities have not been performed. [10][11][12] Interestingly, in 2006, Wee and colleagues reported that the C-H insertion reaction proceeded when using diazoester 5 with a lactam unit structurally related to our substrate 1 13) (Chart 2). The research group successfully synthesized a core framework of the bioactive natural product from C-H inser-* To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 98%